Finance and Legal Foundations of Managing Investment Risks in Professional Sport - O. V. Litvishko; V. G. Keschyan (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
Since Russian economy passed over to market relations and the International Olympic Committee changed its view on the problem of professionalism and amateurishness the issues of professionalization of higher achievement sport and its shift to the commercial channel have been discussed. Due to low demand for the final product of professional sport, different structures of financing overseas and Russian sport clubs have been developed. While the most important source of financing for overseas teams that carry out planning  on the micro-level and set a goal to maximize profits is proceeds from commercial activity, such source for Russian teams that in conditions of market relations could not find a relevant number of customers, often because of low quality of the sport product is sponsors’ money and budget funds. The transfer of sport organizations to self-financing implies search for new sources of filling items of budget revenue, raising efficiency of finance management and their assessment as investment projects. The absence of necessary legal regulation and stimulation of business activity in the field of professional sport can lead to its misbalance and inefficiency of management. The authors put forward a number of mechanisms, which could stimulate professional clubs to raise effectiveness of using budget resources directed to sport industry and to optimize the process of planning investment policy of state in respect of this field of activity in order to obtain social and economic effect.